A Concise History of the Modern World - Woodruff, William. author. aut Link
XII, 401 p.
Keywords: By investigating the major changes in world history during the past five hundred years, Woodruff explains to what extent world forces have been responsible for shaping both the past and the present. This extraordinary book tells of the rise and fall of empires and civilizations; it recounts the growing communality and interdependence of nations; it shows how so many problems of the contemporary world are the legacy of an unprecedented era of western domination - the end of which was hastened by the two world wars. In explaining how the world has come to be what it is, the author examines the implications surrounding the end of the cold war, the unravelling of communism in Eastern Europe, and the growing challenge of the non-western world to western superiority. It is Woodruff's belief that we have reached a crucial transitional stage in world history in which the world will no longer be shaped by the single image of western modernism, but increasingly by the image of all cultures and civilizations. With the shift of geopolitical and geoeconomic power to Asia, and with the growing world-wide influence of religious fundamentalism and revolutionary nationalism, the need for a global perspective has become acute. A Concise History of the Modern World encompasses the learning and the insights gleaned by the author from a life-time career as a world historian.